Graphics processing units: more than the way to realistic video games (2011)
The huge market of the video games has propelled the development of hardware and software focused on making the game environment more realistic. Among such developments are the graphics processing units (GPU), which are intended to alleviate the central processing unit (CPU) of the host computer from the computation that creates “life” for the video games. GPUs reach this goal with the use of multiple computation cores operating on a parallel architecture; these features have made the GPUs attractive for more than the development of video games. In this paper is presented a brief description of the features of CUDA™, a parallel computing architecture on GPUs. The application of the GPUs on the numerical reconstruction of holograms from a digital in-line holographic microscope is shown. On doing this task an 11-fold speeding up with respect to the same calculation done on a typical CPU is reached.